Sinterbility of (Bi1-xLaxTi3O12 ceramics - P. Siriprapa (2018)
This research studied the effects of sintering temperature and La 3+ doping content on phase, microstructure and densification of bismuth lanthanum titanate (Bi4-xLaxTi3O 12; BLT) ceramics when x = 0, 0.25, 0.5, 0.75 and 1.0, respectively. The BLT powders were prepared using a mixed-oxide method. The mixtures were calcined at 750°C for 4 h before being pressed and sintered at 1000-1150°C for 4 h. The result of phase analysis by X-ray diffraction (XRD) indicated the existence of orthorhombic phase for all sintering temperatures. The XRD peak intensities of the ceramics showed preferred orientation of a particular set of {001}-type planes. The ceramics mainly composed of plate-like grains. Increasing the sintering temperature increased grain size and increased preferred grain orientation. The present of La3+ in BLT ceramics reduced preferred orientation especially at higher sintering temperature. Results of microstructural investigation agreed well with X-ray diffraction patterns. © 2008 Trans Tech Publications, Switzerland.